Application of Laku Pandai (Branchless Banking) in The Legal Perspective of Sharia Banking in Indonesia - Abdurrahman Hakim (RaSAIL Media Group, Semarang, Indonesia, 2024)
This research examines the increasing standardization of sharia banking services for people who have not yet received banking services (unbanked and underbanked). This requires legal certainty to protect customers and Sharia bank agents when running the Laku Pandai (Branchless Banking) application. This research uses qualitative methods, literature studies, and normative-doctrinal legal research. The collected data was analyzed using deductive logic with a statutory approach. The analysis techniques used are qualitative analysis and content analysis. This research indicates that implementing an inclusive financial system in Indonesia is still not in line with applicable regulations and real policies. This does not fulfill the sense of justice and legal certainty needed to protect customers and bank agents.